Convex functions and functions with bounded turning - Tuneski,Nikola (Tamsui Oxford Journal of Mathematical Sciences)
Let A be the class of analytic functions in the unit disk U=｛z:|z|<1｝ that are normalized with f(0)=f'0(0)-1=0 and let -1≤B